El espectro autista y la vida psicosocial en los pacientes del Pamuniq Quevedo año 2019 - Carrera Guerrero, Guisella Dayana (2019)
The main objective of this work was to determine the impact of the autistic spectrum on the psychosocial life of patients in the Pamuniq Quevedo year 2019, this was based on a literature and field investigation, obtaining as a solution to the problem a psycho-pedagogical proposal for intervention with activities both daily and social. Therefore, the results show expectations regarding the effectiveness of the work and with possible real, measurable and observable results. It is important to highlight the relevance of the aspects chosen to work, due, on the one hand, to the frequent lack of characteristic autonomy of these patients with an autistic spectrum and, on the other, to the significant deficiencies in social development suffered by people with autism. Therefore, being able to favor these areas can significantly improve the psychosocial and family life, as well as facilitate the performance of the educational work of the Pamuniq Board. The acquisition of daily life skills is a challenge in the life of any patient who is within a normalizing criterion. For those affected by the Autistic Spectrum, it sometimes becomes an impossible goal. Advancing in overcoming the different milestones of development means approaching new possibilities of integral well-being. In proposal, aspects considered basic have been worked on: sphincter control, hygiene, clothing and food. The effectiveness in the results of these activities implies a substantial and positive change in the child's life